Rebranding Produk Kopi Excelsa Oleh Kelompok Masyarakat KOPI GUNUNG Dengan Packaging Baru dan Digital Marketing - Zainal Abidin Achmad; Yenny Wuryandari; Kusuma Wardhani Mas’udah; M. Husni Tamrin (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2022)
Coffee is a leading commodity in Jombang Regency. One of these coffee varieties is Excelsa Coffee. The main obstacle for coffee farmers and traders in Sumberjo Village is the processing of excelsa coffee which is quite complicated. The Grant Program for Application of Research Results for the Community (PIHAT) aims to foster community groups KOPI GUNUNG in Sumberjo Village, Wonosalam District, Jombang Regency to have knowledge and skills in coffee plant care and digital marketing. The results of the identification of the problem of Pokmas KOPI GUNUNG as a partner, the PIHAT team provides solutions in the form of a) Increasing knowledge and skills in caring for coffee plants, b) Improving the quality of new labels and packaging, c) Creating Instagram accounts and making marketing support profile videos, and d) Digital marketing training. After partners gain knowledge and skills in caring for coffee plants, knowledge of digital marketing skills, and producing coffee product packaging, the goal of implementing this PIHAT program is to increase sales of coffee products from the KOPI GUNUNG community group with the brand and packaging